Daily effects of face-to-face and cyber incivility via sadness, anger and fear. Issue 2 (3rd April 2022) - Niven, Karen; Connolly, Catherine; Stride, Christopher B.; Farley, Samuel
ABSTRACT: Many workers are subjected to incidents of rudeness and ignorance at work. Emerging evidence suggests that exposure to such incivility has an immediate impact on people's well-being and commitment. In this article we contribute to this nascent area of enquiry by investigating the role of discrete emotions in explaining how exposure to incivility translates into detrimental daily consequences, and by examining whether the role of emotions varies depending on whether incivilities occur during face-to-face versus online interactions. In a diary study of 69 workers, we find that face-to-face incivility has a pronounced daily impact on workers' exhaustion and turnover intention, and that this impact is mediated by increased feelings of sadness and anger, but not fear. In contrast, cyber incivility only affects workers' emotional exhaustion as a result of increases in sadness. Our findings provide insight into the mechanisms of daily effects of workplace incivility and the divergent daily effects of face-to-face versus cyber incivility.